Clay Shoveler's Fracture: A Pain in the Neck - Marc Boutros; Maria R. Karam; Maria El Asmar; Emmanuelle Wakim; Labib Chebli; Pierre Maurice Doumit Bader Tarabay; Sami Roukoz (Spine Surgery and Related Research)
Clay shoveler's fracture is a stable spinous process fracture commonly occurring at the seventh cervical vertebrae. The name originated in Australia during the 1930s, after many reports of similar injuries among clay workers who suffered fractures due to a sudden flexion force on their neck and back muscles, hence the name “clay shoveler's fracture.” This fracture may occur as a consequence of a direct blow/trauma, a contraction of the shoulder muscles, and sudden extreme movements of the neck influenced by additional factors presented throughout the article. Clay shoveler's fracture mechanisms vary among different age groups; Schmitt's disease is the juvenile version. Although this fracture was initially associated with clay shoveling, it occurs in modern-day sports and activities such as paddling, weightlifting, volleyball, Wii gaming, and many more. A rare occurrence, clay shoveler's fracture is frequently misdiagnosed. Hence, many characteristics were pinpointed to help distinguish it from other differential diagnostics. What does a clay shoveler's fracture patient feel? What are the best tools for the physical exam and imaging? These questions will be answered and developed in this article to reach the right diagnosis and correct treatment for the patient.